2009
DOI: 10.1007/s11596-009-0528-z
|View full text |Cite
|
Sign up to set email alerts
|

Dose distribution verifications of IMRT for NPC

Abstract: In order to explore a dose distribution verification procedure of intensity modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC) and establish its evaluation criteria, we performed 35 two-dimensional (2D) patient-specific IMRT verifications over the year 2006. The percent of pixels passing gamma and the normalized agreement test (NAT) index were mainly used to represent the agreement between the measured and computed dose distributions with three criteria (2%/2 mm, 3%/3 mm and 5%/3 mm) as reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Each of these criteria has been suggested elsewhere. 2,7,21,22 The choice of the criteria is made so that as much information as possible can be obtained and observed. The dose differences between measured dose (in Linac) and calculated dose (in TPS) are evaluated while suppressing the dose of 10%, 20% or 30% from dose distribution.…”
Section: Dose Measurements Using 2d-arraymentioning
confidence: 99%
“…Each of these criteria has been suggested elsewhere. 2,7,21,22 The choice of the criteria is made so that as much information as possible can be obtained and observed. The dose differences between measured dose (in Linac) and calculated dose (in TPS) are evaluated while suppressing the dose of 10%, 20% or 30% from dose distribution.…”
Section: Dose Measurements Using 2d-arraymentioning
confidence: 99%
“…Previous studies on heat transfer processes have mostly been conducted at atmospheric pressure, with limited research conducted under negative or low-pressure conditions. Li et al [9][10][11] conducted experimental, simulation, and theoretical analyses to investigate the heat transfer performance and driving comfort of heat exchangers under different pressures. The study by Li et al 9 investigated the heat transfer performance of radiators under different atmospheric pressures and revealed the signicant inuence of atmospheric pressure on the convective heat transfer coefficient on the air side through theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [9][10][11] conducted experimental, simulation, and theoretical analyses to investigate the heat transfer performance and driving comfort of heat exchangers under different pressures. The study by Li et al 9 investigated the heat transfer performance of radiators under different atmospheric pressures and revealed the signicant inuence of atmospheric pressure on the convective heat transfer coefficient on the air side through theoretical analysis. Despite the study's theoretical insights, it requires experimental validation to corroborate its ndings.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research studies have indicated that lotus root polysaccharides (LRPs) possess antioxidant, antidiabetic, antiobesity, antilipidemic and immunomodulatory activities and that they would have high value in the commercial development of functional food and medicine. 3,9,10 Quality control is considered to be the main issue in the commercialization process of functional polysaccharide products. 11 So far, little is known about the quality control of LRPs.…”
Section: Introductionmentioning
confidence: 99%